Public Sector Innovation Through Web Marriage Management Information System - Zahara Syafira; Asima Yanti Sylvania Siahaan (Program Pascasarjana Universitas Negeri Makassar, 2024)
Improving the quality of public services is carried out by the government, one of which is by creating public service innovations. SIMKAH (Nikah Management Information System) is present as a public service innovation related to marriage registration services at the website-based District KUA. The research method carried out at the Office of Religious Affairs (KUA) of Tanjung Morawa District, Deli Serdang Regency using a qualitative descriptive approach with 5 variables including Relative Advantage, Compatibility, Complexity, Triability and Observability. The results showed that the SIMKAH is an update of the marriage registration service which was originally manual to online so that the service delivery becomes effective and efficient. This can be seen from the five indicators in the theory of innovation attributes, only in the complexity indicator that there are still obstacles, namely technical problems such as system error network problems and lack of human resources who specifically manage this application, as well as the complexity that can be seen from the understanding and ability of the community to access online services that cannot be generalized. So that improvements are needed from the central system of the Ministry of Religion and socialization to the community regarding the use of SIMKAH innovations in marriage registration services. Data uniformity and integrated data backup in marriage registration services is very necessary to provide solutions to existing problems with the previous service system.